Bridge engineering handbook - Chen, Wai-Fah, 1936-; Duan, Lian (Taylor & Francis, 2014)
Over 140 experts, 14 countries, and 89 chapters are represented in the second edition of the Bridge Engineering Handbook. This extensive collection provides detailed information on bridge engineering, and thoroughly explains the concepts and practical applications surrounding the subject, and also highlights bridges from around the world.